PEMANFAATAN TEKNOLOGI DIGITAL DALAM INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Annisa Rizki Wardani; Syauki Habibi Muhammad; Imam Syafi’i (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This article examines the use of digital technology in innovative Islamic Religious Education (IRE) instruction at SMPN 2 Gresik. Rapid technological advancements require teachers to adapt their teaching approaches to be more interactive, contextual, and aligned with the characteristics of the digital generation. This study aims to identify the forms of digital technology utilization in PAI instruction, the innovations implemented by teachers, and their impact on student motivation and learning effectiveness. Employing a qualitative case study approach, data were collected through observation, in-depth interviews with PAI teachers, students, and the school principal, as well as documentation related to digital learning tools. The results indicate that teachers utilize various digital media such as Google Classroom, YouTube, Quizizz, Canva, and interactive educational videos to enhance students’ understanding and participation. Learning innovations like blended learning, the flipped classroom, and digital gamification have proven effective in boosting students’ motivation, engagement, and religious awareness. Although challenges exist, such as limited digital literacy and technological resources, teachers can overcome these through adaptive strategies and collaboration among educators. This study concludes that digital technology plays a crucial role in transforming Islamic Education (PAI) and reinforcing Islamic values through creative approaches relevant to the digital age.